Challenges of a simplified opt-out consent process in a neonatal randomised controlled trial: qualitative study of parents' and health professionals' views and experiences. Issue 3 (2nd November 2020) - McLeish, Jenny; Alderdice, Fiona; Robberts, Helen; Cole, Christina; Dorling, Jon; Gale, Chris
Abstract : Background: More effective recruitment strategies like alternative approaches to consent are needed to facilitate adequately powered trials. Witholding Enteral feeds Around Transfusion was a multicentre, randomised, pilot trial that compared withholding and continuing feeds around transfusion. The primary clinical outcome was necrotising enterocolitis. The trial used simplified opt-out consent with concise parent information and no consent form. Objective: To explore the views and experiences of parents and health professionals on the acceptability and feasibility of opt-out consent in randomised comparative effectiveness trials. Methods: A qualitative, descriptive interview-based study nested within a randomised trial. Semistructured interview transcripts were analysed using inductive thematic analysis. Setting: Eleven neonatal units in England. Participants: Eleven parents and ten health professionals with experience of simplified consent. Results: Five themes emerged: 'opt-out consent operationalised as verbal opt-in consent', 'opt-out consent normalises participation while preserving parental choice', 'opt-out consent as an ongoing process of informed choice', 'consent without a consent form' and 'choosing to opt out of a comparative effectiveness trial', with two subthemes: 'wanting "normal care"' and 'a belief that feeding is better'. Conclusion: Introducing a novel form of consent proved challenging in practice. The principle of a simplified, opt-out approach to consent was generally considered feasible and acceptable by health professionals for a neonatal comparative effectiveness trial. The priority for parents was having the right to decide about trial participation, and they did not see opt-out consent as undermining this. Describing a study as 'opt-out' can help to normalise participation and emphasise that parents can withdraw consent.